HUBUNGAN MANAGERIAL OVERCONFIDENCE, KEPEMILIKAN PEMERINTAH DAN KEPUTUSAN PEMBIAYAAN PERUSAHAAN - Dewi Puji Lestari; Faisal Faisal (Jurnal Ekonomi dan Bisnis, 2019)
This study examines the effect of managerial overconfidence on corporate financing whichmeasured by leverage ratio. Also it investigates the moderating effect of government ownershipon the relationship between managerial overconfidence and leverage. The managerialoverconfidence is measured by photo profile, degree of education, experience, gender andnetwork. The sample consists of 176 public companies listed on Indonesia Stock Exchange in2017. The results of this study show that managerial overconfidence proxied by photo profile hasa negatively effect on leverage. Other results find that experience and network positively affecton leverage. However, this study failed to show that level of education, gender, governmentownership have significant effect on leverage. In addition, government ownership does not actas a moderating variable that influence the relationship between managerial overconfidence andleverage. The implications of this study suggest that the personal characteristics of managersuch as profile, experience and network should be considered as factors that may influencelevel of corporate financing.Keywords: managerial overconfidence, government ownership, financing, leverage, upperechelon theory